Uncovering the mechanism leading to the synthesis of symmetric and asymmetric Tröger's bases - Lanza, Priscila Ailín (2019)
Tröger´s bases have been attracting great interest due to their potential applications in nanoelectronics, supramolecular chemistry, molecular recognition, biological activity and auxiliaries for asymmetric synthesis. However, a detailed step by step proposal for the mechanism leading to the production of these compounds is still uncovered. A set of five model syntheses of symmetric and asymmetric Tröger´s base derivatives starting from substituted anilines and formaldehyde was done and envisaged as representative for understanding the underlying mechanism. All reasonable pathways were thoroughly scanned by means of DFT calculations. The highest energy TS was associated with the entrance of the first formaldehyde which produces the first out of three key carbocations. The last step, the closure of the methylene-bridged diazocyne heterocycle was also found of kinetic relevance and as a source of stable intermediates or byproducts. The whole mechanistic picture would provide keys for the rational planning of the synthesis of these compounds.